DIMENSIONAMENTO DE ESPÉCIES FORRAGEIRAS EM UM SISTEMA SILVIPASTORIL DE PINUS ELLIOTTII - Hampel, Brenda Jacoboski; Bianchi, Cleusa Adriane Menegassi; Avila, Cilene Fátima De Jesus; Kommers, Daniela Regina; Lucchese, Osório Antônio; Schiavo, Jordana (Salão do Conhecimento, 2019)
Projeto de pesquisa realizado no curso de agronomia da Unijuí.